Development of a brief psychological intervention for perinatal depression (BIND‐P). (24th October 2020) - Ransing, Ramdas; Kukreti, Prerna; Raghuveer, Pracheth; Mahadevaiah, Mahesh; Puri, Manju; Pemde, Harish; Karkal, Ravichandra; Patil, Suvarna; Nirgude, Abhay; Kataria, Dinesh; Sagvekar, Shraddha; Deshpande, Smita N.
Abstract: Background: Lack of recognition in national programs, poor referral system, and non‐availability of trained human resources are the important barriers for the delivery of perinatal depression (PND) services in low‐ and middle‐income countries (LAMICs). To address this there is an urgent need to develop an integrative and non‐specialist‐based stepped care model. As part of its research thrust on target areas of India's National Mental Health Programme (NMHP), the Indian Council of Medical Research funded a research project on the outcome of PND at four sites. In this article, we describe the development of the primary health care worker‐based stepped care model and brief psychological intervention for PND. Methods: A literature review focused on various aspects of PND was conducted to develop a model of care and intervention under NMHP. A panel of national and international experts and stakeholders reviewed the literature, opinions, perspectives, and proposal for different models and interventions, using a consensus method and WHO implementation toolkit. Results: A consensus was reached to develop an ANM (Auxillary nurse midwife)‐based stepped‐care model consisting of the components of care, training, and referral services for PND. Furthermore, a brief psychological intervention (BIND‐P) was developed, which includes the components of the low‐intensity intervention (eg, exercise, sleep hygiene). Conclusion: The BIND‐P model and intervention provide a practical approach that may facilitate effective identification, treatment, and support women with PND. We are currently evaluating this model across four study sites in India, which may help in the early detection and provision of appropriate and integrative care for PND.